1996
DOI: 10.1021/om950968h
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer in Valence-Trapped Mixed-Valence 2,1‘:3,2‘:2‘‘,1‘‘‘:3‘‘,2‘‘‘-Tetrakis(propane-1,3-diyl)-1,1‘‘- biferrocenium Triiodide:  Structural, Electrochemical, and Mössbauer Characteristics

Abstract: The X-ray structure determinations of the mixed-valence 2,1‘:3,2‘:2‘‘,1‘‘‘:3‘‘,2‘‘‘-tetrakis(propane-1,3-diyl)-1,1‘‘-biferrocenium triiodide and the corresponding neutral biferrocene and the effects of the interannular trimethylene bridges on the intramolecular electron-transfer rates in both solid and solution states are reported. The X-ray structure of the mixed-valence triiodide salt has been determined at 298 K. The corresponding neutral biferrocene crystallizes in a hexagonal space group. In common with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Here r is the adiabatic chargetransfer distance (estimated as 5.1, 5.0, and 7.3 for [1 + ], A + , and trans-B + , respectively, based on X-ray crystallography); e max is the molar absorptivity at the band maximum; (Dn 1/2 ) obs is the band half-width, which was determined by using the high energy half of the peak and then multiplied by a factor of 2. [b] From Reference [15]; similar data were reported with I 3 À as the counterion in CH 2 Cl 2 ; [54] see also other related studies. [10,20,49,53] [c] From reference [15]; data with PF 6 À as the counterion in CD 2 Cl 2 at infinite dilution are very different with l max = 2100 nm; [19] see also other related studies.…”
Section: à4supporting
confidence: 69%
“…Here r is the adiabatic chargetransfer distance (estimated as 5.1, 5.0, and 7.3 for [1 + ], A + , and trans-B + , respectively, based on X-ray crystallography); e max is the molar absorptivity at the band maximum; (Dn 1/2 ) obs is the band half-width, which was determined by using the high energy half of the peak and then multiplied by a factor of 2. [b] From Reference [15]; similar data were reported with I 3 À as the counterion in CH 2 Cl 2 ; [54] see also other related studies. [10,20,49,53] [c] From reference [15]; data with PF 6 À as the counterion in CD 2 Cl 2 at infinite dilution are very different with l max = 2100 nm; [19] see also other related studies.…”
Section: à4supporting
confidence: 69%
“…Notably, grinding of the triclinic polymorph of [Fv{Fe(C 5 H 4 CH 2 Ph} 2 ] + I 3 -, although having little effect on its powder diffraction pattern, results in the appearance of some trapped Mo ¨ssbauer signals at room temperature, whereas the original material is detrapped at least as low as 25 K. 77 Distortion of the two cyclopentadienyl rings of the bridging fulvalene ligand from planarity in the crystal structures of the triiodide of multiply-bridged species such as that shown in Figure 4g is believed to account for its fully Mo ¨ssbauer trapped behavior. 81,82 The introduction of interannular bridges into biferrocene derivatives may lead to tilting of the cyclopentadienyl rings, both in solution and the solid state. Dong et al have suggested ring tilt will lead to increased mixing of the ferrocene HOMO with the orbitals of the bridging ligand, and thus to increased metal-metal interaction in the bridged species.…”
Section: Bimetallocenesmentioning
confidence: 99%
“…Distortion of the two cyclopentadienyl rings of the bridging fulvalene ligand from planarity in the crystal structures of the triiodide of multiply-bridged species such as that shown in Figure g is believed to account for its fully Mössbauer trapped behavior. , …”
Section: Fulvalene Systemsmentioning
confidence: 99%
“…Usually they are classified in three categories: intramolecularly bridged mononuclear systems in which the two cyclopentadienyl rings are linked with one2a or several hydrocarbon chains (“super phanes”),2b intermolecularly bridged mononuclear compounds connected with other aromatic rings,2c and polynuclear species 2d. Of particular interest is the influence of structural deformations on the properties of metallocenophanes, the intervalence transfer of electrons in binuclear moieties, and the electric conductivity. In subsequent studies one or even several methylene groups in metallocenophanes were replaced by heteroatoms such as oxygen, sulfur, silicon, and others .…”
Section: Introductionmentioning
confidence: 99%